Pengaruh Sosialisasi Peraturan Perpajakan Dan Pemahaman Peraturan Perpajakan Tentang Insentif Pajak UMKM Terhadap Kemauan Menjalankan Kewajiban Perpajakan UMKM Di Masa Pandemi Covid-19 (Studi Kasus Pada Mitra Driver Ojek Online Di Daerah Depok) - Jumalil Syahroni; Rahadi Pratomo Singgih (Jurnal Ilmu Administrasi Publik, 2021)
The phenomenon behind this research is problems related to the willingness to carry out tax obligations, which are related to tax regulations campaigns and understanding tax regulations for MSME taxpayers. In this study the author used a quantitative approach to produce accurate data. Quantitative methods are used because this study aims to measure variables, conduct a sampling process, and prove the hypothesis statistically. Based on the results of the study, it is known that the regression coefficient value of the tax regulation campaign variable is positive, i.e. +0.108. The results of the T-test found tcount < ttable (0.689 <1.988) with sig value (0.493) > (0.05), which means that the tax regulation campaign on MSME tax incentives has a positive but not significant effect on the willingness to carry out MSME tax obligations during the Covid-19 pandemic among online ojek (motorcycle taxi) driver partners in the Depok area.The regression coefficient value of the understanding of tax regulations is positive, i.e. +0.312. The results of the T-test found tcount < ttable (2.096 <1.988) with sig value (0.493) > (0.05), which means that understanding of tax regulations regarding MSME tax incentives has a positive and significant effect on willingness to carry out MSME tax obligations during the Covid-19 pandemic among ojek driver partners in the Depok area. Meanwhile, the F-count test produced a value of 6.011, which is greater than the F-table (6.011 > 3.105), and a significance value of 0.004, where p < 0.05 (0.004 < 0.05). This means that the campaign and understanding of tax regulations regarding MSME tax incentives simultaneously affect the willingness to carry out MSME tax obligations during the Covid-19 pandemic among ojek driver partners in the Depok area.